Previous investigations on the influence of oxygen concentration on nitrogen removal efficiency in a hybrid moving bed sequencing batch biofilm reactor (MBSBBR) = Oczyszczanie ścieków w reaktorach ze złożem ruchomym - możliwości technologiczne - Żubrowska-Sudoł, Monika; Podedworna, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents preliminary results of the research on the efficiency nitrogen removal in a hybrid sequencing batch reactor MBSBBR operating at low dissolved oxygen (DO) concentration ranging between 0,5 and 2 mg O_2/l. The study was carried out in a pilot scale model of SBR with a total volume of 35 liters, filled with carrier media up to the volumetric ratio 7,5 % of the fill volume.
Keywords: oczyszczalnia ścieków; reaktor sekwencyjny; dissolvet oxygen concentration; MBSBBR; nitrogen removal